Temporal genetic variation in populations of Diplodus sargus from the SW Mediterranean Sea - Gonzalez-Wanguemert, Mercedes (2007)
Population genetic studies on white sea bream Diplodus sargus have revealed different patterns in the subdivision of populations in the Mediterranean Sea. However, the stability of observed allele frequencies over time remains poorly tested. The aim of this study was to show that the genetic structure of D. sargus could significantly change over time by analysing temporal variations in allozymes. In order to determine temporal variation in the genetic structure of 5 natural D. sargus populations in the SW Mediterranean, we screened 14 allozyme loci. Our main finding was the significant genotypic differentiation among cohorts (year-classes) in the Guardamar (FST = 0.012; p < 0.001) and Cape of Palos (FST = 0.008; p < 0.001) populations. The differentiation observed in the present study when considering pair-wise comparisons between cohorts is similar to that of all populations throughout the Mediterranean Sea. Our results suggest that microgeographical variations, also known as ‘chaotic genetic patchiness’, could occur in D. sargus populations from the SW Mediterranean. The recruitment of genetically variable cohorts at 1 site each year may account for these variations. We also discussed alternative explanations for this genetic pattern. This study confirms the importance of understanding the ecology, behaviour and environment of fish populations when investigating population genetic structure. Our results also highlight the importance of incorporating temporal samples when conducting population structure studies.